Eggs of Perlidae (Insecta, Plecoptera) of the Russian Far East - Teslenko, Valentina A. (Zootaxa, 2024)
Eggs of 12 perlid species from the Russian Far East are examined and described based on scanning electron microscopy images. Morphological features of the chorion and extrachorion, including egg attachment structures, vary considerably among genera and species and may be useful for their recognition. The Korean species Neoperla goguryeo Murányi & Li, 2015 is recorded in the Russian Far East for the first time.